Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/jcpt.13330
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced external counterpulsation: A unique treatment for the “No‐Option” refractory angina patient

Abstract: What is known and objectives Coronary artery disease (CAD) is the leading cause of death in the United States. For patients on whom guideline‐driven measures have been tried, enhanced external counterpulsation (EECP) is the only truly noninvasive and safe intervention for which a reduction of angina symptoms and nitrate use, increased exercise tolerance, and improvement in myocardial ischaemia have been shown. The objective of this study was to demonstrate, by way of literature review, the efficacy of EECP as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The results of this study showed that the adherence rate of CHD patients to EECP treatment after discharge was only 24.23%, which was similar to the adherence to exercise training programs in cardiac rehabilitation (16,17). Studies have proved that adhering to a complete course of EECP treatment can not only improve the cardiac function of CHD patients, relieve the onset of angina, but also improve their sleep, anxiety, depression, and thus improve the quality of life (18)(19)(20)(21). However, the dropout rate of CHD patients after discharge was quite high in this study.…”
Section: Discussionmentioning
confidence: 53%
“…The results of this study showed that the adherence rate of CHD patients to EECP treatment after discharge was only 24.23%, which was similar to the adherence to exercise training programs in cardiac rehabilitation (16,17). Studies have proved that adhering to a complete course of EECP treatment can not only improve the cardiac function of CHD patients, relieve the onset of angina, but also improve their sleep, anxiety, depression, and thus improve the quality of life (18)(19)(20)(21). However, the dropout rate of CHD patients after discharge was quite high in this study.…”
Section: Discussionmentioning
confidence: 53%
“…Treatment with EECP is a safe, non-invasive extracorporeal circulation method that is widely used for cardiac-cerebral vascular diseases to reduce angina symptoms and the use of nitrates, increase exercise tolerance, and improve myocardial ischemia ( 18 ). It could also improve the quality of life of patients with cardiac failure ( 19 ), and have a positive effect on the hemodynamics of the coronary and carotid arteries ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 75% of patients are responders to EECP treatment, and these benefits are often sustained for from 3 to 5 years. [59][60][61] EECP is limited by a number of contraindications: coagulopathy with an international normal ratio of more than 2.5, arrhythmias, severe peripheral arterial disease, venous disease, and severe chronic obstructive pulmonary disease. 62 It is important to note that to the best of our knowledge, the majority of studies of EECP have investigated its use in stable angina rather than exclusively in RAP patients.…”
Section: External Enhanced Counterpulsationmentioning
confidence: 99%